Conducting community-led research using trail cameras to develop baseline wandering domestic cat local abundance estimates - Elizabeth A. Gow; Ben Aubrey; Lydia Cossar; Carter Mazerolle; Edward Cheskey (Canadian Science Publishing, 2024)
Assessing cat local abundance provides information on where wandering cat numbers are highest and what habitats or factors are associated with wandering cats. A variety of stakeholders can lead this research and then use the findings to make scientifically informed decisions to guide the physical locations of cat management actions. Here, we document a framework that engages community members, uses minimal equipment (six trail cameras), and provides scientifically derived information for interested parties to inform, direct, or test the effectiveness of cat management practices. Using these methods in Gatineau, Quebec, Canada, we demonstrate how we estimated cat population size and cat local abundances across a variety of co-variates while accounting for non-perfect detection by using 55 trail camera sites and N-mixture models. Urban areas had three-fold higher local wandering cat abundances than parkland areas, and neighbourhoods below the median income had the highest local abundances of wandering cats. We estimated there are between 8905 and 48,419 (mean 21,298) wandering cats in Gatineau, with 18%-73% of those cats being unowned. These findings can be used to identify locations for future cat management. If estimates of cat abundance are repeated, they can assess the effectiveness of management actions.